An essential role of the JIP1 scaffold protein for JNK activation in adipose tissue - Jaeschke, Anja (Cold Spring Harbor Laboratory Press, 2004)
The c-Jun NH(2)-terminal kinase (JNK) is activated during obesity. One consequence of obesity is that JNK phosphorylates the adapter protein insulin receptor substrate 1 (IRS-1) on Ser 307 and inhibits signaling by the insulin receptor. JNK can therefore cause peripheral insulin resistance during obesity and may contribute to the development of type 2 diabetes. Here we report that the JNK-interacting protein 1 (JIP1) scaffold protein, which binds components of the JNK signaling module, is essential for JNK activation in the adipose tissue of obese mice. These data identify JIP1 as a novel molecular target for therapeutic intervention in the development of obesity.